2002
DOI: 10.1097/00007632-200204010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Study and Digital Modeling of Traction Resistance in Posterior Thoracic Implants

Abstract: Screw fixation is the most appropriate from a mechanical point of view. During tests, however, screw fixation falls short of its promises. This leads to the hypothesis that in most cases screws pull out because the bony anchoring of the pedicle screwing fails. Screws are less effective if their anchoring in the pedicles cannot be guaranteed, which is probably the reason for their relative weakness. Screw diameter should be chosen according to the size of each pedicle. The findings showed that hooks impose addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
2
14
0
4
Order By: Relevance
“…By mechanical testing, we found that the 6.0 mm screw had a higher pullout strength than the 5.0 mm screw. These results agree with those reported by Kwok et al, Barber et al, and Gayet et al, [11,26,28].…”
Section: Discussionsupporting
confidence: 94%
“…By mechanical testing, we found that the 6.0 mm screw had a higher pullout strength than the 5.0 mm screw. These results agree with those reported by Kwok et al, Barber et al, and Gayet et al, [11,26,28].…”
Section: Discussionsupporting
confidence: 94%
“…Although offset hooks may enhance the pedicle screw construct when placed at the adjacent level, extending the fusion an additional level might also be considered. Gayet et al [6] investigated the traction resistance and mode of failure of posterior thoracic implants in single human motion segments. Pedicular-laminar traction resulted in fracture at the base of the pedicles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tension transmission will occur in a more appropriate manner from the screw to the pedicle. 8 Qualitatively speaking, we found that in addition to the region near medullar canal, at the medial surface of screw's end as compared to the lateral surface, a higher concentration of tensions was seen. This is probably due to the fact that when we apply pullout strength to the screw, the photoelastic model tends to spin over its own axis, counter-clockwise, because the screw is not centered on the model.…”
Section: Referencesmentioning
confidence: 59%
“…the ones identified by Gayet et al 8 who conducted a study using a finite elements method in vertebral models, simulating pullout strength. The authors carried out mechanical pullout assays in order to validate the method employed on the finite element; in these assays, they found that pedicle fractures occurred on sites showing the highest concentration of tension.…”
Section: Referencesmentioning
confidence: 99%